Adaptasi Visual Momiji dengan Teknik Crochet pada Produk Fashion - Feny Puspitasari; Annisa Amalia; Yumeida Rahmah (JURNAL RUPA, 2023)
Momiji is one of the natural beauty that must be enjoyed in autumn in Japan. Momiji beautiful colors range from red, orange, to yellow. This beauty makes Japanese people make the tradition of Momiji hunting when autumn arrives. The beauty of Momiji in Japan inspired the making of autumn party dresses by applying the beauty of autumn Momiji colors and the shape of maple leaves as a decorative structure in dress, using crochet techniques. Crochet is a technique to create fabric using a needle that has one end, producing a fabric with various textures and structures while forming a motif. The texture produced by this crochet technique depends on the type of crochet stitch that is arranged. One type of stitch used in this party dress is maple leaf. The purpose of this research is as an effort to develop crocheting skill art which is generally used for daily linen and clothing products. The party dress is a sleeveless midi-dress (made by using acrylic yarn) equipped with a stole (made by decofur yarn). By adapting the shape and color of Momiji using this crochet technique, it produces a warm party dress to cope with the nature of autumn which is a transition from summer to winter.